Policy Brief 9: Informal networks and what they mean for anti-corruption practice - Baez Camargo, Claudia; Costa, Jacopo; Kassa, Saba (Basel Institute on Governance Policy Briefs, 2022)
Corruption is frequently associated with money alone and the behaviours of a few individual “bad apples” operating in otherwise healthy governance systems. This is too simplistic. As the latest research shows, including research in Tanzania and Uganda on which this Policy Brief is based, corruption is a networked phenomenon. This Policy Brief explains what this means and its implications for anti-corruption practice. When ordinary citizens and business people face problems, like constrained access to public services or an uneven playing field, they invest time, effort and resources in building informal networks. Held together by personal connections and corrupt payments, these informal networks are a problem-solving mechanism. They allow members – such as business people, other citizens and public officials – to pursue a variety of goals. The networks aid in easing access to public services, for example, or helping a business to run smoothly, or securing business opportunities with the government. Informal networks can be leveraged to speed up long and complicated permit processes or exploit weaknesses in formal tender processes to obtain undue access to contracts. When red tape is used by public officials to extort bribes from service users, informal networks can help manage and overcome these demands. In contexts in which these informal networks are widespread, the research shows that conventional anti-corruption measures, such as introducing more regulations, policies and controls, can actually backfire and increase corruption. Breaking this self-reinforcing cycle of networked corruption requires a shift in thinking and approaches: Focusing on networked corruption as opposed to individual corrupt behaviours. Tackling corruption both from the demand and the supply side by addressing inefficiencies and weaknesses in public systems that cause problems for ordinary citizens and business people. This may make it less likely that they will resort to corruption through informal networks to overcome the public service weaknesses. Harnessing informal networks for anti-corruption objectives. This includes leveraging new insights into social norms and networks and establishing Collective Action initiatives to better target the underlying drivers of corruption. This Policy Brief presents findings from a research project entitled “Harnessing informality: Designing anti-corruption network interventions and strategic use of legal instruments”, funded by UK Aid as part of the Global Integrity Anti-Corruption Evidence Programme (GI-ACE).